2021
DOI: 10.3390/molecules26216706
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Acidic Chitinase Effectively Degrades Random-Type Chitosan to Chitooligosaccharides of Variable Lengths under Stomach and Lung Tissue pH Conditions

Abstract: Chitooligosaccharides exhibit several biomedical activities, such as inflammation and tumorigenesis reduction in mammals. The mechanism of the chitooligosaccharides’ formation in vivo has been, however, poorly understood. Here we report that mouse acidic chitinase (Chia), which is widely expressed in mouse tissues, can produce chitooligosaccharides from deacetylated chitin (chitosan) at pH levels corresponding to stomach and lung tissues. Chia degraded chitin to produce N-acetyl-d-glucosamine (GlcNAc) dimers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…We previously reported that the degradation products from β-chitin with higher D.D. were more abundant in comparison with αchitin [37,38]. In addition, the degradation products differ significantly between blockand random-type chitosan due to the substrate specificity of mouse Chia [38].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We previously reported that the degradation products from β-chitin with higher D.D. were more abundant in comparison with αchitin [37,38]. In addition, the degradation products differ significantly between blockand random-type chitosan due to the substrate specificity of mouse Chia [38].…”
Section: Discussionmentioning
confidence: 94%
“…were more abundant in comparison with αchitin [37,38]. In addition, the degradation products differ significantly between blockand random-type chitosan due to the substrate specificity of mouse Chia [38]. The blocktype chitosan has amorphous regions with highly deacetylated areas (GlcN-rich), while in the random-type chitosan, the GlcNAc and GlcN residues are interspersed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations